2019
DOI: 10.1007/s00520-019-04901-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of low anterior resection syndrome on quality of life in patients with mid or low rectal cancer

Abstract: Synopsis: Defecatory problems may occur after low anterior resection with total mesorectal excision. This study evaluated the incidence of these problems and their impact on quality of life in patients who underwent surgery for mid or low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
1
29
1
4
Order By: Relevance
“…The influence of body mass index on the functional results of sphincter-preserving treatment was not confirmed in the process of meta-analysis. However, this factor was described as significant in some publications: for example, in the study by Bohlok et al [16], which included 43 patients after low anterior resection with a total mesorectal excision, 31 (72.1%) had signs of severe functional impairment, while BMI> 30 kg/m 2 was the only statistically significant risk factor for major LARS (p=0.047), which, nonetheless, could be detected due to a small sample size of patients in that study. Almost all authors of the studies included in our meta-analysis distinguished the factor of preventative ostomy as unfavorable in terms of functional results.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of body mass index on the functional results of sphincter-preserving treatment was not confirmed in the process of meta-analysis. However, this factor was described as significant in some publications: for example, in the study by Bohlok et al [16], which included 43 patients after low anterior resection with a total mesorectal excision, 31 (72.1%) had signs of severe functional impairment, while BMI> 30 kg/m 2 was the only statistically significant risk factor for major LARS (p=0.047), which, nonetheless, could be detected due to a small sample size of patients in that study. Almost all authors of the studies included in our meta-analysis distinguished the factor of preventative ostomy as unfavorable in terms of functional results.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that nearly half of the patients who underwent TME suffered from major LARS [34]. Bohlok et al (2019) also showed that a large proportion (72.1%) of patients after TME complained of LARS to different extents [35]. A meta-analysis done by Kidane et al also proposed the viewpoint that TEM could be adopted as a reliable device which provides similar oncological control but lower mortality rate [36].…”
Section: Discussionmentioning
confidence: 99%
“…Opposingly, previous studies perceived female patients aged 50 to 79 to have a higher proportion of Major LARS and worse functional outcome, while age remains a subject of controversy between studies correlating young age to worse LARS scores and those not nding a signi cant correlation. [27][28][29][30] Postoperative bowel dysfunction is a major health issue and its burden on patients quality of life is sometimes underestimated [31]. In Arabic communities, such manifestations may also have a strong cultural component which not only increases the quality of life impediment [32], but also represents a hurdle to adequate care due to shame and miscommunication.…”
Section: Discussionmentioning
confidence: 99%